Assessing the quality of the overall training program and outcome of research for higher degrees at the Faculty of Medicine, University of Colombo, during the past 6 years - Fernando, M.D.M.; Gunawardena, G.S.A.; Karunaweera, N. D. (My University, 2012)
Doctoral education is meant to create and sustain an intellectual community. It trains another generation of professional researchers and academics. Hence, with the enormous importance of assessing quality of doctoral education comes the need for accountability. It leads to development of strategies to improve the quality of research degrees produced by the institutions and provide a reliable guidance for selection of doctoral programs.